2014
DOI: 10.1002/ejlt.201300381
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition, lipid oxidation, and fishy odour development in seabass (Lates calcarifer) skin during iced storage

Abstract: Changes in fatty acid profile, lipid hydrolysis and oxidation, development of fishy odour and volatile compounds in seabass (Lates calcarifer) skin during 18 days of iced storage were investigated. Peroxide value (PV) increased up to Day 6 and subsequently decreased up to 18 days (p < 0.05). The continuous increases in thiobarbituric acid reactive substances (TBARS) values, free fatty acid (FFA) content and lipoxygenase (LOX) activity were noticeable with increasing storage time (p < 0.05). Formation of FFA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 47 publications
3
40
1
Order By: Relevance
“…Hexanal, heptanal and 1‐octen‐3‐ol are generated from n − 6 polyunsaturated fatty acid oxidation (Iglesias and Medina ). Sae‐leaw and Benjakul () found that seabass skin lipid contained high level of linoleic acid (9.29 g/100 g lipid), which could be oxidized to yield the products.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hexanal, heptanal and 1‐octen‐3‐ol are generated from n − 6 polyunsaturated fatty acid oxidation (Iglesias and Medina ). Sae‐leaw and Benjakul () found that seabass skin lipid contained high level of linoleic acid (9.29 g/100 g lipid), which could be oxidized to yield the products.…”
Section: Resultsmentioning
confidence: 99%
“…1‐Octen‐3‐ol is an important contributor to off‐flavor due to its low odor threshold and was reportedly formed from oxidation of arachidonic acid by 12‐lipoxygenase (Hsieh and Kinsella ). Seabass skin lipid contained arachidonic acid at a level of 1.88 g/100 g lipid (Sae‐leaw and Benjakul ). Thiansilakul et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During ice storage of fish a series of biochemical changes occur at a relatively rapid pace. The changes involve both nitrogen compounds (Huidobro et al 2001) and the lipid fraction (Widjaja et al 2009, Saeleaw andBenjakul 2014). Among different mechanisms responsible for fish deterioration during storage on ice, lipid damage, through hydrolysis and oxidation reactions of the lipid fraction, can lead to important losses in nutritive value and quality during chilled storage (Šimat et al 2015).…”
Section: Introductionmentioning
confidence: 99%